The role of risk perception and entrepreneurial orientation in the planning response of small firms. - Neo, Zhi Wei. (2012)
Various studies have been conducted over the past decades to examine the relationship between risk perception and planning responses of firms. The concept of entrepreneurial orientation has also been a keen topic of interest to academics and businessmen alike. Nevertheless, research on the above-mentioned relationships has largely been conducted in the context of medium and large firms, with little focus on small businesses. In light of this apparent knowledge gap, this paper seeks to focus on small firms with the context set in a highly uncertain environment, using the local automobile industry as a proxy. Through a broad review of literature, elements identified as essential to build small firm theory as delineated by d’Amboise and Muldowney (1988) and the resource dependency framework developed by Pfeffer and Salancik (1978) served as the foundation for this research.